2013
DOI: 10.1103/physreva.87.032317
|View full text |Cite
|
Sign up to set email alerts
|

Why entanglement of formation is not generally monogamous

Abstract: Unlike correlation of classical systems, entanglement of quantum systems cannot be distributed at will: if one system A is maximally entangled with another system B, it cannot be entangled at all with a third system C. This concept, known as the monogamy of entanglement, is manifest when the entanglement of A with a pair BC can be divided as contributions of the entanglement between A and B and A and C, plus a term τ ABC involving genuine tripartite entanglement and so expected to be always positive. A very im… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…We should also point out that for pure states of three qubits there is a conservation law between discord and EF, such that E 12 + E 13 = D 12 + D 13 [11]. So the monogamies of the two quantum correlations are tightly connected, and a violation of one would imply of the other, something already noted before by some of us [16]. These relations are obtained from the Koashi-Winter (KW) relation E 12 + J ← 13 = S 1 [4], where J ← 13 is the one-way classical correlation between 1 and 3 [17,18].…”
Section: B Monogamy For the Linear Versionmentioning
confidence: 62%
“…We should also point out that for pure states of three qubits there is a conservation law between discord and EF, such that E 12 + E 13 = D 12 + D 13 [11]. So the monogamies of the two quantum correlations are tightly connected, and a violation of one would imply of the other, something already noted before by some of us [16]. These relations are obtained from the Koashi-Winter (KW) relation E 12 + J ← 13 = S 1 [4], where J ← 13 is the one-way classical correlation between 1 and 3 [17,18].…”
Section: B Monogamy For the Linear Versionmentioning
confidence: 62%
“…A way to deal with this might involve a hybrid approach to monogamy of correlations, when both quantum and classical correlations are present, as suggests. Finally, (Fanchini et al, 2011b) argue that the relationship between quantum and classical correlations is at the heart of why entanglement of formation is not monogamous.…”
Section: Monogamy Of Discordmentioning
confidence: 99%
“…It should be noted that, in the monogamy relation, the square of concurrence is monogamous other than the concurrence itself which is not monogamous. Previous studies indicated that the QD is not monogamous even in three-qubit pure states [25][26][27][28][29], which does not imply that the square of QD is not monogamous either.…”
Section: A Definitions and Monogamous Conditionmentioning
confidence: 99%